2018
DOI: 10.1016/s0140-6736(17)33106-9
|View full text |Cite|
|
Sign up to set email alerts
|

Preliminary aggregate safety and immunogenicity results from three trials of a purified inactivated Zika virus vaccine candidate: phase 1, randomised, double-blind, placebo-controlled clinical trials

Abstract: Departments of the Army and Defense and National Institute of Allergy and Infectious Diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
161
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(170 citation statements)
references
References 27 publications
3
161
0
Order By: Relevance
“…The results from the first 3 trials indicate that recipients developed robust neutralizing antibody titers that on transfer into mice significantly reduced or eliminated viral titers following ZIKV challenge. 74 Adverse effects were reported by 84% of recipients but were relatively minor (eg, pain or tenderness at injection site, fatigue, headache, malaise).…”
Section: Current Status Of Vaccine Developmentmentioning
confidence: 99%
“…The results from the first 3 trials indicate that recipients developed robust neutralizing antibody titers that on transfer into mice significantly reduced or eliminated viral titers following ZIKV challenge. 74 Adverse effects were reported by 84% of recipients but were relatively minor (eg, pain or tenderness at injection site, fatigue, headache, malaise).…”
Section: Current Status Of Vaccine Developmentmentioning
confidence: 99%
“…In addition, an mRNA vaccine encoding the prM and E genes of a French Polynesian strain induced strong CD4+ T cell and neutralizing antibody responses in non-pregnant mice and protected mice and NHP from virus challenge (118). Importantly, it was recently reported that an inactivated virus vaccine was safe in humans and elicited neutralizing antibody responses that were higher than the protective threshold observed in animal studies (119). Several additional clinical trials testing different vaccine platforms including inactivated virus, DNA, mRNA, virus-vector and synthetic peptide vaccines are ongoing.…”
Section: Maternal Immunization To Protect Infants From Neonatal Pamentioning
confidence: 99%
“…Three ZIKV purified inactivated virus vaccine (ZPIV) phase I clinical trials (NCT02963909, NCT02952833, and NCT02937233 ) were reported as a combined interim analysis of the preliminary results for the identical group for each individual study 51 . These studies (Table 2) were conducted at Walter Reed Army Institute of Research (WRAIR), Silver Spring, MD, United States; Saint Louis University, Saint Louis, MO, United States; and Beth Israel Deaconess Medical Center (BIDMC), Boston, MA, United States.…”
Section: Vaccines In Clinical Trialsmentioning
confidence: 99%